A Therapeutic Stance Addressing Destructiveness: What We Can Learn From Looking Back at the Experience with Schiffian Reparenting. (2nd January 2022) - Gheorghe, Nicoleta; Brunke, Marina; Deaconu, Diana; Gheorghe, Alexandra; Ionas, Lucia
Abstract: Although violent outbursts were common among residential patients undergoing Schiffian reparenting, reflection on their meaning was not integrated into reparenting theory. This article looks at how reparenting theory approached destructiveness and then explores other contributions from transactional analysis theory and beyond. Drawing from this analysis, the authors share their own reflections on what they see as blind spots in the Schiffian approach with a focus on destructiveness. They also look at how these dynamics may be found in daily practice. A case illustration highlights how destructiveness may be acknowledged and worked through in the psychotherapy office. As an emerging alternative, the authors introduce the concept of therapeutic stance.